A new perspective for the application of the Activity Based Costing method in manufacturing companies using MES class systems - Hadław, Maciej; Żabiński, Tomasz (Nowa perspektywa zastosowania metody Activity Based Costing w firmach produkcyjnych wykorzystujących systemy klasy MES, 2020)
The purpose of this paper is to present a new perspective for the practical use of the Activity Based Costing method for cost accounting in manufacturing companies using modern MES systems. In this example, the data from a company in the metal industry has been studied. The article shows how the use of software for automatic registration of data from machines can significantly eliminate the disadvantages of the Activity Based Costing method and contribute to relevant optimization in the field of product costing. The calculations were made based on the example of one manufacturing machine carrying out three different production orders. It was shown that operating at the interface between IT and financial analysis can bring the desired benefits in the field of data analysis automation and the elimination of human error thanks to the use of hardware and software platforms integrating the latest IT and industrial automation solutions
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 2 (56), s. 30-42
Keywords: activity based costing; MES; data collection optimization; optymalizacja gromadzenia danych